Las regiones fértiles de la tierra: nueva propuesta crítica a Plu., De facie 938D - Pérez-Jiménez, Aurelio (My University, 2015)
This paper trays to resolve the syntactical problem posed by the datives of the comparative phrase ὥσπερ ἄκροις τισὶν ἢ χερρονήσοις ἀνέχουσιν ἐκ βυθοῦ (Plu., De facie 938D), by changing into ἀνεχούσης the plural dativ ἀνέχουσιν we read in the codices E and B. On the other side, and as a consequence of the above solution, the author proposes to pay a greater attention to the alternative ἄκραις (instead of ἄκροις) which Turnebus and the Basilensis offer, may be as a lecture coming from a lost manuscript.
Contribución al XII Congreso de la Sociedad Española de Plutarquistas (trienal).
Keywords: Plutarco - Crítica e interpretación; De Facie in orbe lunae; Nota crítica